Memory function in opioid-dependent patients treated with methadone or buprenorphine along with benzodiazepine: longitudinal change in comparison to healthy individuals - Rapeli Pekka; Fabritius Carola; Kalska Hely; Alho Hannu (BMC, 2009)
Abstract Background Opioid-substitution treatment (OST) for opioid dependence (OD) has proven effective in retaining patients in treatment and reducing illegal opiate abuse and crime. Consequently, the World Health Organization (WHO) has listed the opioid agonists methadone and buprenorphine as essential drugs for OD that should be available worldwide. In many areas of the world, OD is often associated with concomitant benzodiazepine (BZD) dependence and abuse, which complicates treatment. However, possible changes in the cognitive functioning of these patients are not well-known. The present study is the first to examine longitudinal stability of memory function in OST patients with BZD use, thus providing a new tool for health policy authorities in evaluating the usefulness of OST. Methods Within the first two months (T1) and between 6-9 months (T2) after OST admission, we followed the working memory, immediate verbal memory, and memory consolidation of 13 methadone- and 15 buprenorphine- or buprenorphine/naloxone-treated patients with BZD dependence or abuse disorder. The results were compared to those of fifteen normal comparison participants. All participants also completed a self-reported memory complaint questionnaire on both occasions. Results Both patient groups performed statistically significantly worse than normal comparison participants in working memory at time points T1 and T2. In immediate verbal memory, as measured by list learning at T1, patients scored lower than normal comparison participants. Both patient groups reported significantly more subjective memory problems than normal comparison participants. Patients with more memory complaints recalled fewer items at T2 from the verbal list they had learned at T1 than those patients with fewer memory complaints. The significance of the main analyses remained nearly the same when the statistical tests were performed without buprenorphine-only patients leaving 12 patients to buprenorphine/naloxone group. Conclusion Working memory may be persistently affected in OST patients with BZD use. A high number of memory complaints among OST patients with BZD use may indicate memory consolidation impairment. These findings show that recovery of memory function in OD patients treated along with BZDs takes time, and their memory complaints may have practical relevance.